Zinc allocation to and within Arabidopsis halleri seeds: Different strategies of metal homeostasis in accessions under divergent selection pressure. Issue 3 (30th November 2020) - Babst‐Kostecka, Alicja; Przybyłowicz, Wojciech J.; Seget, Barbara; Mesjasz‐Przybyłowicz, Jolanta
Abstract: Vegetative tissues of metal(loid)‐hyperaccumulating plants are widely used to study plant metal homeostasis and adaptation to metalliferous soils, but little is known about these mechanisms in their seeds. We explored essential element allocation to Arabidopsis halleri seeds, a species that faces a particular trade‐off between meeting nutrient requirements and minimizing toxicity risks. Combining advanced elemental mapping (micro‐particle induced X‐ray emission) with chemical analyses of plant and soil material, we investigated natural variation in Zn allocation to A. halleri seeds from non‐metalliferous and metalliferous locations. We also assessed the tissue‐level distribution and concentration of other nutrients to identify possible disorders in seed homeostasis. Unexpectedly, the highest Zn concentration was found in seeds of a non‐metalliferous lowland location, whereas concentrations were relatively low in all other seed samples—including metallicolous ones. The abundance of other nutrients in seeds was unaffected by metalliferous site conditions. Our findings depict contrasting strategies of Zn allocation to A. halleri seeds: increased delivery at lowland non‐metalliferous locations (a likely natural selection toward enhanced Zn‐hyperaccumulation in vegetative tissues) versus limited translocation at metalliferous sites where external Zn concentrations are toxic for non‐tolerant plants. Both strategies are worth exploring further to resolve metal homeostasis mechanisms and their effects on seed development and nutrition.